Metabolomics and molecular docking-directed antiarthritic study of the ethyl acetate extract from Celastrus orbiculatus Thunb. (10th August 2022) - Lv, Mengying; Liang, Qiaoling; Wan, Xiayun; Wang, Zheng; Qian, Yayun; Xiang, Jie; Luo, Zhaoyong; Ni, Tengyang; Jiang, Wei; Wang, Weimin; Wang, Haibo; Liu, Yanqing
Abstract: Ethnopharmacological relevance: Celastrus orbiculatus Thunb., an important folk medicine, has long been used for the treatment of rheumatoid arthritis and its ethyl acetate extract (COE) has been reported to possess anticancer, antiinflammation and antiarthritic effects. However, the therapeutic effect and mechanism of COE treatment in rheumatoid arthritis has been rarely studied especially from the perspective of metabolomics. Aim of study: To reveal the therapeutic effects of COE on adjuvant–induced arthritis (AIA) rats through histopathological analysis, non-targeted metabolomics, and molecular docking study. Materials and methods: Forty-three Wistar rats were randomly divided into normal group, AIA model group, methotrexate group, and COE groups (80 mg/kg, 160 mg/kg and 320 mg/kg of ethyl acetate extract). Paw swelling and arthritis score were monitored through the experiment. Serum levels of tumor necrosis factor α (TNF-α) and nitric oxide were determined and histopathological evaluation was performed. Furthermore, Ultra-high performance liquid chromatography-linear trap quadrupole-Orbitrap-based metabolomics was employed to characterize metabolic changes of AIA rats after COE treatment and molecular docking was performed to predict the potential phytochemicals of COE against TNF-α. Results: COE at three dosages could significantly relieve paw swelling and reduce arthritis scores of AIA rat. Histopathological analysis revealed remarkable decrease in synovial inflammation and bone erosion after COE treatment, especially at middle and high dosage. Additionally, COE down-regulated serum levels of TNF-α and nitric oxide. Serum metabolomics showed that 22 potential biomarkers for the COE treatment of AIA rats were identified, which were closely related to fatty acid metabolism, glycerophospholipid catabolism, and tryptophan metabolism. The molecular docking models predicted that olean-type triterpenes in COE may contribute most to therapeutic effects of rheumatoid arthritis through targeting TNF-α. Conclusions: COE could significantly relieve the arthritic symptoms in AIA rats and the ultra-high performance liquid chromatography-mass spectrometry based metabolomics proved to be an efficient method to characterize subtle metabolic changes of AIA rats after COE treatment. Graphical abstract: Image 1